PEMBENTUKAN KARAKTER GREEN BEHAVIOR PADA GENERASI MILENIAL DALAM MENINGKATKAN PENGGUNAAN ECO-PRODUCT - Imam Sapuan (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2020)
effect of greenhouse gases produced by plastic waste is one of the causes of thehotter temperature. The purpose of this study is to determine the MillennialGeneration's Green Behavior Characteristics in Increasing the Use of EcoProducts. The study employs qualitative methodologies, with data gatheredthrough a literature review. The study's findings reveal that the idea of protectingthe environment is growing in line with global warming. Environmental concernsare frequently linked to the future. That is, long-term rather than short-termconsequences are predicted from pro-environmental initiatives and greenbehavior. Millennials are a more future-oriented generation, thus they are willingto forego current gratification in order to accomplish better long-term goals.Millennials are willing to invest time and resources in present activities that willhave a long-term impact, and they are willing to put up with an uncomfortablecircumstance in the short term if it will lead to a better future.